2019
DOI: 10.5267/j.dsl.2019.6.002
|View full text |Cite
|
Sign up to set email alerts
|

On the use of multi-criteria decision making methods for minimizing environmental emissions in construction projects

Abstract: There are huge amounts of emissions associated with construction industry during its different stages from cradle till building demolition. This study presents a methodology that integrates multi-objective optimization and multi-criteria decision making (MCDM) in order to enable construction decision-makers to select the most sustainable construction alternatives. Four objectives functions are investigated, which are: construction time, lifecycle cost, environmental impact and primary energy in order to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Koganti et al (2019) applied a hybrid MCDM method of GRA-AHP-TOPSIS for supplier selection problem. Marzouk and Abdelakder (2019) used weighted sum model (WSM), COP-RAS and TOPSIS method to minimize the environmental emissions in construction projects and also proposed that these three methods provide the best ranking of the alternatives.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Koganti et al (2019) applied a hybrid MCDM method of GRA-AHP-TOPSIS for supplier selection problem. Marzouk and Abdelakder (2019) used weighted sum model (WSM), COP-RAS and TOPSIS method to minimize the environmental emissions in construction projects and also proposed that these three methods provide the best ranking of the alternatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…COPRAS (Zavadskas et al, 2008) and ARAS (Zavadskas & Turkis, 2010;. Many researchers adopted these two techniques and used it as a decision making tools to solve problems in different areas like environmental issues (Marzouk & Abdelakder, 2019), education (Das et al, 2012), agricultural problems (Iisik & Adali, 2016), vendor selection (Chatterjee and Bose, 2013a;madic et al, 2014) etc. but very few works has been reported that these methodologies is being utilized for solving the decision problems associated with our daily life and the selection of electronic gadgets e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These extensions have been widely used by the researchers to address the problems such as multi-criteria decision making (MCDM), multi-criteria group decision making (MCGDM), classification and pattern recognition etc. (see, e.g., [8][9][10][11][12][13][14][15][16][17][18]).…”
Section: Introductionmentioning
confidence: 99%
“…The final output results for the best suppliers of raw materials are LI, PA, and SL for fabrics, dyes, and wax respectively. Marzouk and Abdelakder (2019) presented an approach to minimize the environmental emissions in construction projects by applying TOPSIS, COPRAS and weighted sum model (WSM).…”
Section: Introductionmentioning
confidence: 99%